Effect of price fairness, service quality, brand imagedand product quality on consumer satisfaction Electric Cars (Ev) in Indonesia - Levi Jose Antonio Horacio Da Costa Serrano; Innocentius Bernarto (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of price fairness, service quality, brand image and product quality on consumer satisfaction of electric cars (EV) in Indonesia. This research was conducted on 200 electric car (EV) consumers in Indonesia. The sample of respondents was selected according to the criteria and data collection questionnaire with a Likert Scale distributed online. In this study, the PLSSEM method was used to analyze the data. The results of the study are that service quality and product quality affect consumer satisfaction of electric car (EV) consumers in Indonesia positively and significantly, while the variables that have no effect are price fairness and brand image.